Surface properties and corrosion resistance of SF6 plasma-treated polyester-based thermoplastic elastomer - Resende, Renato Carvalho [UNESP]; Waldman, Walter Ruggeri; da Cruz, Nilson Cristino [UNESP]; Durrant, Steven F. [UNESP]; Rangel, Elidiane Cipriano [UNESP] (Wiley, 2018)
Copolyester thermoplastic elastomers (COPE) have interesting mechanical properties but low chemical resistance in aggressive environments. Developing a treatment that would increase their chemical resistance while preserving their convenient bulk characteristics would be an advance. Radiofrequency plasma treatments in sulfur hexafluoride were undertaken. Surface properties and corrosion resistance of untreated and treated samples were investigated. Surface chemical composition was altered, resulting in a loss of organic elements and the incorporation of fluorine. Surface morphology and topography were changed by the removal of species during the treatment. Treatment tends to increase hydrophobicity; for the longer treatment times, hydrophobicity tends to be retained even after aging under atmospheric conditions. Resistance to chlorine attack was substantially increased upon fluorination, while resistance to oxygen attack was improved in some cases. The improvement in the corrosion resistance, which suggests an increase in lifetime under practical conditions, depends on fluorine incorporation and its effect on the physical stability of the structure.
Keywords: cold plasma; COPE; fluorination; hydrophobicity